Increased Measured GFR and Proteinuria in Children with Previous Infection by SARS-CoV-2: Should We Be Concerned? - Alessia Marcellino; Silvia Bloise; Carmelo Pirone; Giulia Brandino; Antonio Barberi; Emanuela Del Giudice; Vanessa Martucci; Mariateresa Sanseviero; Flavia Ventriglia; Riccardo Lubrano (Microorganisms)
Over the past 3 years, several kidney complications in children with severe involvement by SARS-CoV-2 have been described. However, literature data are still lacking regarding possible kidney injury in children with paucisymptomatic SARS-CoV-2 infection. Thus, we retrospectively evaluated renal function in those patients. Children between 3 and 18 years, without any renal disease, with previous paucisymptomatic SARS-CoV-2 infection from May 2020 to March 2022, were recruited at our post-COVID-19 outpatient clinic. We retrospectively collected: Glomerular filtration rate, Fractional-excretion-of-sodium (FENa), tubular-reabsorption-of-phosphate (TRP), calcium-creatinine-urine ratio (CaU/CrU); proteinuria/m2/day and microhematuria by urine cytofluorometry. A total of 148 children were enrolled after a median period of 3 (IQR 6) months after infection. Twenty-six patients (17.6%) had reduced GFR, fifty (33.9%) had hyperfiltration, eleven (7.4%) had abnormal FENa and/or TRP, twenty-two (14.9%) had hypercalciuria, seventy-eight (52.7%) had pathological daily proteinuria. Microhematuria was found in sixteen (10.9%) subjects. Hyperfiltration was more prevalent among males (38.9% vs. 22.4%, p = 0.027); CaU/CrU [median 0.08 (IQR 0.09) vs. 0.13 (IQR 0.13) p = 0.003] was significantly higher in females. Our data suggest that SARS-CoV-2 could determine, in a significant proportion of children, kidney damage characterized by hyperfiltration, proteinuria, and hematuria, warranting strict follow-up in these patients.